2013
DOI: 10.1016/j.jinteco.2012.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Are all trade protection policies created equal? Empirical evidence for nonequivalent market power effects of tariffs and quotas

Abstract: The steel industry has been protected by a wide variety of trade policies, both tariff-and quotabased, over the past decades. This extensive heterogeneity in trade protection provides the opportunity to examine the well-established theoretical literature predicting nonequivalent effects of tariffs and quotas on domestic firms' market power. Robust to a variety of empirical specifications with U.S. Census data on the population of U.S. steel plants from 1967-2002, we find evidence for significant market power e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…However, they do not speak directly about their impact on market power, which cannot be directly measured in the absence of information on the entire set of firms, both foreign and domestic. In that sense, we view our article as complementary to these works: We focus on a 8 Blonigen et al (2013) estimate a positive but mostly insignificant effect on market power. Konings and Vandebussche (2005) and Pierce (2011) find significant evidence of enhanced market power for EU and U.S. firms, respectively, whereas Nieberding (1999) and Rovegno (2013) (2018), which discusses the different methods (production based or demand based) that have been used to estimate markups.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, they do not speak directly about their impact on market power, which cannot be directly measured in the absence of information on the entire set of firms, both foreign and domestic. In that sense, we view our article as complementary to these works: We focus on a 8 Blonigen et al (2013) estimate a positive but mostly insignificant effect on market power. Konings and Vandebussche (2005) and Pierce (2011) find significant evidence of enhanced market power for EU and U.S. firms, respectively, whereas Nieberding (1999) and Rovegno (2013) (2018), which discusses the different methods (production based or demand based) that have been used to estimate markups.…”
Section: Introductionmentioning
confidence: 97%
“…Our article is close to a number of papers that examine the role of trade policy and trade reforms on market power and pricing behavior. For instance, looking at the U.S. steel industry and using plant-level census data, Blonigen et al (2013) find that, as suggested by traditional theory, quota-based protection increases the market power of domestic producers whereas tariff-based protection does not. Kim (2000) provides similar results based on Korean sector-level data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, quotas that allow domestic firms to avoid competition may remove the incentive to invest if efficiency improvements are less necessary without foreign competition. Furthermore, there are numerous theoretical and empirical papers indicating that quotas increase monopoly power and collusion compared to tariffs (See Bhagwati (1965), Feenstra (1988), Krishna (1989), and Blonigen et al (2013)). However, even if quotas do enhance market power more than tariffs, it is not clear that this would result in greater investment.…”
Section: Empirical Model and Datamentioning
confidence: 99%
“…17 We also control for the level of import penetration (Import Penetration it ). Our inclusion of import penetration follows Blonigen et al (2013), which compares the impact of tariff protection and quota protection on markups in the US steel industry. Blonigen et al (2013) argue that to isolate and compare the impact of quota and tariff protection, it is necessary to control for the level of import penetration, and we concur.…”
Section: Empirical Model and Datamentioning
confidence: 99%